Phenolic Compounds from Apples: Reviewing their Occurrence, Absorption, Bioavailability, Processing, and Antioxidant Activity – a Review - Małgorzata Starowicz; Bohdan Achrem–Achremowicz; Mariusz K. Piskuła; Henryk Zieliński (Polish Journal of Food and Nutrition Sciences)
This review summarises the research on phenolic compounds in apples in relation to their geographical origin, cultivars, technological processes, and human health effects due to their antioxidant activity and bioavailability. Apples are popular among consumers and are known as a rich source of vitamins, minerals, and biologically active compounds. In this review article, we have focused on their phenolic compounds. Some epidemiological studies have confirmed the protective effects of apples against chronic diseases, which can be linked to the high content of phenolics in plant tissues and their bioavailability. However, according to the available literature, the geographical origin and variety of apples influence the content of these bioactive compounds and are highly related to their antioxidant activity fluctuation. The gathered studies have confirmed that the choice of polyphenol-rich raw material as well as proper processing are important to achieve high-quality fruit-based products with a high content of antioxidants after a few stages of production. It was proven that the processing of apples could significantly modify the content of phenolics in the finished products, including juices, concentrates, vinegars, and ciders. For instance, the use of high pressure or vacuum has been proposed as a highly potent solution in inhibiting flavonoid degradation during intensive processing. Moreover, several methods have been screened to monitor the phenolic content and antioxidant activity of apple samples, based on spectrophotometry, HPLC, LC-MS, and LC-MS/MS techniques for chemical compound separation and identification. The main assumptions of these techniques and results obtained are described in this review.